Mesopotamian cylinder seal from Lori Berd (Armenia): An object in an unusual location? - Davtyan, Ruben (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Archaeological Site: Lori Berd (Northern Armenia); cemetery, dating from Middle Bronze Age till Achaemenid period. Tomb No. 106: stone chamber. Ceramic and part of the finds date to Achaemenid period. Also a pinkish chalcedony cylinder seal with gold caps on gold pin. Iconography: standing figure, seizing two upstanding caprids surrounded by symbolic fillings. Dating: a Neo-Babylonian cylinder seal of late 8th till 7th century BC. Similar example: usage of Neo-Assyrian/Babylonian cylinder seal by Irtashduna (wife of Darius I) around 500 BC. Interpretation: suitable for reciprocity of gifts in prestige-goods system of Achaemenid period. Perhaps a gift from satrap to local chief.